Biomechanical evaluation of a new intramedullary nail compared with proximal femoral nail antirotation and InterTAN for the management of femoral intertrochanteric fractures - Wang, ChaoFeng; Duan, Ning; Li, Zhong; Ma, Teng; Zhang, Kun; Wang, Qian; Huang, Qiang (Frontiers in Bioengineering and Biotechnology, 2024)
Surgical treatment is the main treatment method for femoral intertrochanteric fractures (FIFs), however, there are lots of implant-related complications after surgery. Our team designed a new intramedullary nail (NIN) to manage such fractures. The purpose of this study was to introduce this new implant and compare it with proximal femoral nail antirotation (PFNA) and InterTAN for treating FIFs.Methods: An AO/OTA 31-A1.3 FIF model was built and three fixation models were created via finite element method, comprising PFNA, InterTAN, and the NIN. Vertical, anteroposterior (A-P) bending, and torsional loads were simulated and applied to the three fixation models. Displacement and stress distribution were monitored. In order to compare PFNA and the NIN deeply, finite element testing was repeated for five times in vertical load case.The finite element analysis (FEA) data indicated that the NIN possessed the most outstanding mechanical properties among the three fixation models. The NIN model had lower maximal stress at implants compared to PFNA and InterTAN models under three load conditions. The trend of maximal stress at bones was similar to that of maximal stress at implants. Besides, the NIN model showed smaller maximal displacement compared with PFNA and InterTAN models under vertical, A-P bending, and torsional load cases. The trend for maximal displacement of fracture surface (MDFS) was almost identical with that of maximal displacement. In addition, there was significant difference between the PFNA and NIN groups in vertical load case (p<0.05).Compared with PFNA and InterTAN, the NIN displayed the best mechanical properties for managing FIFs, including the lowest von Mises stress at implants and bones, and the smallest maximal displacement and MDFS under vertical, A-P bending, and torsional load cases. Therefore, this study might provide a new choice for patients with FIFs.